Toward resilient agriculture and environmental protection: The role of cell wall-bound phenolics - Hura, Tomasz; Hura, Katarzyna; Ostrowska, Agnieszka; Urban, Karolina (Journal of plant physiology, 2023)
Due to their unpredicted scope, duration, and effects, soil droughts pose a serious threat to agriculture. Gradual steppe formation and desertification of farming and horticultural lands are the consequences of climate change. Irrigation systems for field crops do not offer the most viable solution, as they depend heavily on freshwater resources, which are currently scarce. For these reasons, it is necessary to obtain crop cultivars that are not only more tolerant to soil drought, but also capable of effective use of water during and after drought. In this article, we highlight the importance of cell wall-bound phenolics in the efficient adaptation of crops to arid environments and protection of soil water resources. •Cell wall-bound phenolics (CWPh) offer multiple benefits for plants and environment.•CWPh increase soil drought and UV tolerance.•CWPh improve plant water status and water use efficiency.•Protection of freshwater resources and limited irrigation of crops.